Blindguide: Multipurpose Portable Stick - Abdul Ayub, Nurul Adilla; Zulkefli, Fatin Najwa; Jasni, Aida Maisarah; Rahim, Nuur Khairun Neesa’; Jamil, Muhammad Fairuz (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
The value of diversity and inclusiveness is becoming more widely acknowledged these days, especially when it comes to marketing goods meant for people with disabilities (OKU). It is important to provide education and knowledge regarding OKU products to guarantee accessibility and meet the varied demands of customers. However, studies show that customers have a serious lack of knowledge about the characteristics and advantages of OKU products, which can result in conflicts and poor purchase choices. Some customers might not see the potential advantages of OKU goods because they believe they are useless or have limited use. Marketers have created creative approaches to successfully sell OKU products to guide this overcome problem. Using social media and digital channels to spread knowledge about the benefits of OKU products is one such strategy. Moreover, the use of inclusive design ideas in product creation ensures that OKU products are simple to use and accessible to people with a variety of abilities. Marketers can boost the attractiveness and usefulness of OKU products to a wider audience by emphasizing accessibility and use, which will encourage usage and improve the brand's impression. To summarise, the successful promotion of OKU products needs a thorough comprehension of customer requirements, focused communication tactics, and a dedication to accessible principles of design. Marketers may encourage increased knowledge and acceptance of OKU products by educating customers and resolving their concerns. This will ultimately help to create a society that is more accessible and inclusive.